Phytochemicals Screening and Antioxidant Potential of Ant Nest Plants From the Nabire Forest With Different Solvents - Sutrisno Adi Prayitno; Dwi Retnaningtyas Utami; Khoiroh Inda Dini; Andalusia Trisna Salsabila; Devi Kartika Sari (Universitas Darussalam Gontor, 2025)
Ant nests (Myrmecodia pendans), characteristic epiphytic flora of Papua, are recognized for harboring diverse bioactive constituents, including phenolics, flavonoids, tannins, saponins, alkaloids, and triterpenoids, which contribute significantly to antioxidant and pharmacological properties. Nonetheless, the concentrations of these secondary metabolites exhibit inconsistency, primarily attributable to variations in solvent polarity and environmental factors in cultivation regions. This investigation soughtto profile and characterize secondary metabolites from ant nests sourced from the Nabire forest, employing solvents of varying polarities—ethanol, methanol, and n-hexane—to evaluate the efficacy of bioactive compound extraction and antioxidant potential. Extraction procedures involved maceration over a 72-hour duration with the aforementioned solvents. The data obtained were then analyzed quantitatively descriptively with an average followed by a standard deviation. Phytochemical screening revealed that all three extracts contained phenolics, flavonoids, tannins, and triterpenoids; however, ethanol and methanol extracts demonstrated robust positive responses for saponins and alkaloids, whereas the n-hexane extract yielded solely triterpenoids and steroids. Quantitative assessments indicated that the 96% ethanol extract exhibited the highest total phenolic content (84.52 ± 2.31 mg GAE/g) and flavonoid content (61.47 ± 1.28 mg QE/g), coupled with the most potent antioxidant activity (IC₅₀ = 78.65 ± 2.11 ppm). The methanol extract displayed moderate efficacy, while n-hexane showed the weakest performance. These findings underscore the substantial influence of solvent selection on the yield of active compounds. Consequently, ethanol is advocated as the optimal solvent for isolating phenolic and flavonoid compounds from Nabire ant nests. Future investigations are proposed, incorporating advanced extraction techniques such as ultrasonic-assisted methods or ohmic heating, alongside detailed profiling via LC-MS to pinpoint predominant bioactive entities.